Salmonella Excludes Salmonella in Poultry: Confirming an Old Paradigm Using Conventional and Barcode-Tagging Approaches - Yang, Yichao; Tellez, Guillermo; Latorre, Juan D.; Ray, Pamela M.; Hernandez, Xochitl; Hargis, Billy M.; Ricke, Steven C.; Kwon, Young Min (Frontiers in Veterinary Science, 2018)
Salmonella is one of the major foodborne bacterial pathogens, and the consumption of contaminated chicken meats is as a primary route of Salmonella transmission into human food chains. However, the mechanism of Salmonella transmission within the chicken flock is not fully understood, including competitiveness among Salmonella strains during chicken infection. The purpose of the present study was to evaluate the competitive exclusion (CE) between different or same Salmonella species consecutively challenged through the oral route. Two different approaches were used to evaluate the CE effect, including tracking Salmonella colonization by wild-type strains with difference in natural antibiotic resistance or DNA barcode-tagged isogenic strains. When day-of-hatch chicks were administered by wild-type S. Typhimurium (ST) on day 1, followed by infection on day 2 by S. Enteritidis (SE) or vice versa, most of the birds were colonized only by the first strains administered (82% by ST or 83% by SE). When similar experiments were performed using two different isogenic barcode-tagged SE strains, Illumina sequencing analysis of the barcode region showed that the first barcode-tagged strains administered were dominant strains, ranging from 92 to 99% of the Salmonella recovered from ceca. These results provide quantitative evidence supporting the CE theory that oral administration of Salmonella will produce predominant inhibition over the subsequent colonization of ceca by the following administration one day later by different or same Salmonella species. We also showed that the use of barcode-tagged isogenic strains in combination with deep profiling of barcodes by Illumina sequencing can serve as a quantitative method for studying complex dynamics of Salmonella infection, transmission and colonization in poultry.